Pengaruh Pelatihan Dan Disiplin Terhadap Kinerja Karyawan Pada PT.Angkasa Pura II (PERSERO) Bandara Kualanamu Sumatera Utara - Try Aprina Br Bangun Try (Akuntansi Prima, 2021)
The object the study is PT. Angkasa Pura II wichh is a companyengaged in avition services. The objective of the study is to test and analize the effect of training and discipline on employee performance at PT. Angkasa Pura II both partially and simultaneously. The research used some theories of training, disipline parrtially and employee performance whivh were tested by using multiple linear regression analysis. The research used a quantitive research approach, this type of researchis descriptive quantitative an the nature of this study is an exsplonary relationship. The research population were employees at PT. Angkasa Pura II with a total of 150 employees. The research samples were drawn by using the Slovin formula so that the samples obtained for the regression test were 109 employees and 30 respondents were used for testing the validity and reliability. The results of the study showed that simultaneously, training and dicipline had positive and significant effect on employee performance at PT. Angkasa Pura II (Persero). Partially, training and discipline have a positive and significant effect employee performance at PT. Angkasa Pura II (Persero). The coefficient of determination test results showed that 73,6% of the variations in the dependent variable of employee performace were affected by training and discipline and the reamining 26,4% explained by other variables not investigated in the research.